2007
DOI: 10.1186/1471-2121-8-20
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of primary and immortalized fibroblast cells derived from the miniature and domestic pigs

Abstract: Background: The pig, Sus scrofa domestica includes both the miniature and commercial domestic breed. These animals have influenced the human life and economies and have been studied throughout history. Although the miniature breeds are more recent and have increasingly been used in a variety of biomedical studies, their cell lines have rarely been established. Therefore, we sought to establish primary and immortal cell lines derived from both the miniature and domestic pig to better enable insight into possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 56 publications
1
31
0
Order By: Relevance
“…Immortalization of porcine fetal fibroblasts by using hTERT alone was shown by Moon et al, (2014). However, other groups were not able to achieve the same results using fibroblasts from miniature or domestic pigs (Oh et al, 2007).…”
Section: Immortalization Of Cells Using Htertmentioning
confidence: 93%
See 1 more Smart Citation
“…Immortalization of porcine fetal fibroblasts by using hTERT alone was shown by Moon et al, (2014). However, other groups were not able to achieve the same results using fibroblasts from miniature or domestic pigs (Oh et al, 2007).…”
Section: Immortalization Of Cells Using Htertmentioning
confidence: 93%
“…Porcine hepatocyte lines were immortalized by the use of SV40LT and hTERT (Pan et al, 2008) which worked also efficient for porcine fibroblasts (Oh et al, 2007). Immortalization of porcine fetal fibroblasts by using hTERT alone was shown by Moon et al, (2014).…”
Section: Immortalization Of Cells Using Htertmentioning
confidence: 99%
“…7) In brief, the continuous expression of SV40T for more than 60 passages increased the level of polyploidy to about 60%. 10) We analyzed the karyotype of SV40-expressing PEF at passage 10 in our study and found that the level of polyploidy was 16.4% (21/128 samples, see Table 1). In the case of the wild-type PEF cells, the level of polyploidy was about 6.5%.…”
Section: Discussionmentioning
confidence: 99%
“…This result is consistent with the previous findings. 10) Although the expression of SV40T was quite effective for establishing cell lines, prolonged expression has been reported to cause chromosomal abnormalities. 7) In brief, the continuous expression of SV40T for more than 60 passages increased the level of polyploidy to about 60%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation